Experimental Investigation on Geopolymer Concrete:- Sustainable and Eco-Friendly Construction Material - Rafeek Amina; Kumar S. Sundar; Susan Raj Indu (MATEC Web of Conferences, 2023)
The research for the new environmental friendly construction material that will match the durability of ancient concrete has provoked interest into the study of alkali activated cementitious systems over the last two decades. It results in the development of Geopolymer Concrete. This paper represents the development of geopolymer mixes of various ratios of fly ash and GGBS and their mechanical properties were studied. aa Literature review on mechanical and durability properties of geopolymer concrete also been done. The ratio of sodium hydroxide to sodium silicate is 1:2 which is kept a constant to prepare the mix and alkaline liquid to binder ratio as 0.70, but changing the concentration of sodium hydroxide solution as 6M, 4M and 3M to prepare the mix Id. i.e. F75G25, F50G50 and F25G75, respectively (where F and G are Fly Ash and GGBS and the numerical value indicates the percentage of replacement of fly ash by GGBS) were prepared in AML laboratory, CSIR-SERC, Chennai. Ambient curing of concrete at room temperature was adopted.The compressive strength at age of 3, 7 and 28 days were determined. The strength of geopolymer concrete was increased with increase in percentage of GGBS in a mix. It was observed that the mix Id F25G75 gave maximum compressive strength for concentration of NaOH as 3M . Leaching of GPC reduces with increase in percentage of GGBS in a mix. Thus the geopolymer concrete have a relatively higher strength.